Aortic root enlargement in patients undergoing mitral and aortic replacement: early outcomes in a sub-Saharan population - Mve Mvondo, Charles; Tchokouani Djientcheu, Carole; Ngo Yon, Laurence Carole; Banga, Douglas Nkomo; Mbele, Richard; Bella Ela, Amos; Giamberti, Alessandro; Frigiola, Alessandro; Menanga, Alain Patrick; Djientcheu, Vincent De Paul; Ngowe, Marcelin Ngowe (Frontiers in Cardiovascular Medicine, 2023)
Introduction Aortic root enlargement (ARE) is often required to avoid patient–prosthesis mismatch (PPM) in young patients undergoing aortic surgery, including those undergoing combined mitral and aortic valve replacement (double valve replacement, DVR). Adding ARE to DVR may increase the operative risk by extending the surgical time. Herein, we review our experience with ARE in patients who underwent DVR. Materials and methods The medical records of 69 patients who underwent DVR at our institution between February 2008 and November 2021 were retrospectively reviewed. The patients were divided into two groups according to the ARE procedure (ARE-DVR: 25 patients; DVR: 44 patients). Descriptive and comparative analyses of demographic, clinical, and surgical data were performed. Results Among the 69 patients who underwent DVR, 35 were women (sex ratio, 0.97). The mean age at surgery was 26.7 ± 13.9 years (range: 7–62 years). Among the 47 patients aged ≤30 years, 40.4% (19/47) were aged between 10 and 20 years, and 6.3% (3/47) were aged <10 years. Patients in the ARE-DVR group were younger (23.3 ± 12.9 years vs. 28.5 ± 14.2 years, p < 0.05). The New York Heart Association Class ≥III dyspnea was the most common symptom (89.9%), with no differences between the two groups. Of all the patients, 84.1% had sinus rhythm. Rheumatic disease was the most common etiology in the entire cohort (91.3%). The mean aortic annulus diameter was 20.54 mm, with smaller sizes found in the ARE-DVR group (18.00 ± 1.47 mm vs. 22.50 ± 2.35 mm, p < 0.05). The aortic cross-clamping duration was greater in the ARE-DVR group (177.6 ± 37.9 min vs. 148.3 ± 66.3 min, p = 0.047). The operative mortality rate was 5.6% for the entire cohort (ARE-DVR: 8% vs. DVR: 4.5%, p = 0.46). Among the patients who underwent echocardiographic control at follow-up, the mean aortic gradient was 19.6 ± 7.2 mmHg (range: 6.14–33 mmHg), with no differences among the groups. Conclusion The association between ARE and DVR did not significantly affect operative mortality. ARE can be safely used whenever indications arise to reduce the occurrence of PPM, especially in young patients with growth potential.